FAKTOR-FAKTOR YANG MEMPENGARUI PILIHAN KARIR DI BIDANG TEKNIK SIPIL MAHASISWA PROGRAM STUDI TEKNIK SIPIL BANGUNAN GEDUNG (D3) FT-UNP - 2095-2099, Hardy Yasri (Universitas Negeri Padang, 2018)
Abstract— This research begins from students choosing to work in the industry due to lack of job opportunities for graduates of Civil Engineering (D3) if in comparison with graduates of Civil Engineering (S1). Seeing the problem, then conducted research that aims to reveal whether the factors that most influence the career choice of students of Civil Engineering Studies Program (D3). This study is a descriptive study with a population of 29 students of class of 2014. Samples were taken using Total Sampling technique. Primary data collected through questionnaire (questionnaire) with the number of statements in the questionnaire as many as 49 points statement. The Secondary Data obtained from the number of students D3 force 2014 is still active. From the research results can be concluded that the influence of each factor of career choice in Civil Engineering Student Department D3 state university Padang are: Internal Factor (Ability of Intelligence = 52.07%, Talent = 49.43%, Interest = 90 , 34%, Attitude = 55,04%, Personality = 52,41, Value = 82,07, Hobby = 82,30%, Achievement = 44,37%, Skill = 60%, Use of leisure time = 70,80%, Aspiration = 69,89%, Work Experience = 38,85%, Knowledge of work world = 83,79%, Physical ability = 45,75%, Personal problems and limitations = 48,51 % and External Factors (Family Environment = 83.97% and Neighborhood peer = 74.48%). Keyword: Career Choice, Civil Engineering.